Transcutaneous Electrical Nerve Stimulation for Pain Management for Women in Labor. Issue 2 (March 2021) - Daniel, Linda; Benson, Jennifer; Hoover, Stephen
Abstract: Purpose: To determine effectiveness of a transcutaneous electrical nerve stimulation (TENS) unit to improve labor pain management and patient satisfaction with overall labor experience among women in labor at term. Study Design: Prospective, exploratory design using convenience sampling. Methods: Pregnant women at term, anticipating a vaginal birth at our tertiary care hospital, were invited to participate in the TENS study to help manage early labor pain. Pain level was assessed on entry into the study and 2 hours post-TENS application using the Wong-Baker FACES® Pain Rating Scale. A TENS satisfaction survey was conducted during postpartum. Pain scores were analyzed using a matched Wilcoxon signed-rank test. Results: There were 272 women enrolled in the study; 255 completed the patient satisfaction survey and 263 had measured pain assessments pre- and post-TENS application. There was a significant reduction in pain scores after application of TENS, (7.09 vs. 6.74, p = 0.02). Most women 78% (199/255) agreed that TENS helped manage early labor pain, 80% (203/255) would recommend TENS for management of early labor pain, and 72% (183/255) would use TENS again. Clinical Implications: TENS therapy provides nurses with an opportunity to offer women a low-cost, low-intervention treatment for managing early labor. TENS provides a distraction from contractions and generates a sense of control to help women manage the discomforts of labor and possibly remain home longer. Abstract : Transcutaneous electrical nerve stimulation (TENS) may be a low cost non-pharmacologic option for pain management during labor. In this study of 272 women in labor, TENS was well received by users and there was a significant decrease in pain scores after application of the device.